A Study of Problems and Solutions for Iraqi Ports (Basra governorate as a Case Study) (Journal of the College of Basic Education, 2026)
The research aims to identify Iraqi ports, their economic activity, their natural and human (civilizational) components, and the problems they face, as well as their location and characteristics. It has a suitable location for establishing ports due to its view of The Arabian Gulf extends through its southern region along a narrow coastal strip. of (65 square kilometers) and also through the Shatt al-Arab, which consists of the confluence of the Tigris and Euphrates rivers, and its length extends from the stronghold to its mouth in the Arabian Gulf (139, 1 km), Which means it is suitable for navigating ships. The research dealt with the natural and human factors that affect ports, and there are others related to the nature of the national economy and the extent of its development, which essentially determine the feasibility of the port’s work or not. These factors take many forms and include the geographical location, i.e. the location of the port. Ports are affected by a direct relationship with the length of the coast ."on the sea. as weIl as cultural factors, planning and economic capabilities, and civilizational factors, they will be unable to meet the expected demand for imports and exports to Iraq in the future.